Differential regulation of soil microecology in crop rotation systems of maize, seed pumpkin, and processing tomato - Liu, Xingxing; Li, Xuyuan; Feng, Menglei; Liu, Xuliang; Zhu, Xiaoyu; Zhang, Yulong; Zhang, Ge; Wang, Aiying (Frontiers in Microbiology, 2025)
Long-term continuous cropping of processing tomatoes in Xinjiang has led to soil degradation and microecological imbalance, severely constraining the sustainable development of the industry. To investigate the mitigation mechanisms of different crop rotation systems, this study established maize-tomato rotation (SZa), pumpkin (for seeds)-tomato rotation (SLa), and continuous cropping control (SSa) treatments in a long-term continuously cropped tomato field. The results demonstrated that compared to SSa, the SLa treatment increased the proportion of large aggregates (>2 mm) by 16.5%, whereas the SZa treatment decreased it by 24.6%. Rotation significantly reduced soil pH (by 5.6%−6.0%) and increased electrical conductivity (by 124%−215%). Enzyme activities responded variably: phosphatase activity increased by 13.9%, while urease and sucrase activities significantly decreased. Microbial α-diversity was significantly enhanced, with the Shannon index for bacteria and fungi increasing by up to 10.3% and 24.3%, respectively. Network analysis revealed that SZa optimized bacterial network complexity, while SLa specifically reduced the abundance of Ascomycota (by 17.5%) and reshaped the fungal community. Notably, the SLa treatment significantly decreased soil total potassium content by 13.6%. This study confirms that both maize and pumpkin rotation can regulate the soil microecology through differentiated strategies, providing an important theoretical basis for optimizing cropping systems of processing tomatoes in Xinjiang.